2018
DOI: 10.1002/cphc.201701044
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assemblies of Zinc Bacteriochlorophyll‐d Analogues Having Amide, Ester, and Urea Groups as Substituents at 17‐Position and Observation of Lamellar Supramolecular Nanostructures

Abstract: Chlorosomes are unique light-harvesting apparatuses in photosynthetic green bacteria. Single chlorosomes contain a large number of bacteriochlorophyll (BChl)-c, -d, -e, and -f molecules, which self-assemble without protein assistance. These BChl self-assemblies involving specific intermolecular interactions (Mg⋅⋅⋅O3 -H⋅⋅⋅O=C13 and π-π stacks of chlorin skeletons) in a chlorosome have been reported to be round-shaped rods (or tubes) with diameters of 5 or 10 nm, or lamellae with a layer spacing of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 98 publications
(177 reference statements)
1
7
0
Order By: Relevance
“…This indicates the presence of the 2 1 screw axis along the c -axis. The 0.69-nm distance between adjacent zinc chlorophyll molecules was similar to previously reported results for microcrystalline of a cadmium BChl- d analog 26 as well as self-assemblies of Zn-3 25 (Fig. 1c, bottom), the 3 1 -hydroxylated analog of Zn-2 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates the presence of the 2 1 screw axis along the c -axis. The 0.69-nm distance between adjacent zinc chlorophyll molecules was similar to previously reported results for microcrystalline of a cadmium BChl- d analog 26 as well as self-assemblies of Zn-3 25 (Fig. 1c, bottom), the 3 1 -hydroxylated analog of Zn-2 .…”
Section: Resultssupporting
confidence: 89%
“…1c) 2024 . Recently, we have reported that a zinc 3 1 -hydroxy-13 1 -oxo-chlorin having amide and urea groups in the 17-substituent self-assembled to form rod-like supramolecular nanostructures with a spacing of 1.4 nm 25 . In this study, we synthesized zinc 3 1 -methoxy-chlorophyll derivatives lacking the 3 1 -hydroxy group, which was requisite for chlorosomal J -aggregation through specific hydrogen bonding (3 1 -O–H∙∙∙O=C-13).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies also presented the ester-containing analogues as control molecules, not showing the same supramolecular structures and strongly coupled J-aggregates, highlighting the important role of having directional H-bonding groups. 76…”
Section: Urea-containing Systemsmentioning
confidence: 99%
“…Firstly, chemical modifications to a chlorin dye (reduced porphyrin) were made to replicate the π–π stacking, hydrogen bonding, and metal–oxygen coordination observed in natural chlorosome supramolecular assemblies, thus enabling spectrally tunable photonic properties. Secondly, a lipophilic oleylamine moiety was conjugated to the chlorin at the 17‐position to anchor these dyes stably within the HDL interior, thus promoting the completion of ordered dye packing, and its sidechain amide group offered additional intermolecular amide hydrogen bonds . Thirdly, a phospholipid monolayer shell resembling the natural chlorosome's exterior lipid monolayer was coated on the hydrophobic porphyrin assembly and constrained with an apolipoprotein mimetic peptide, bestowing the controlled size and favorable biological behavior of HDL.…”
Section: Figurementioning
confidence: 99%